Cross-Dressing and Transgender Representation in Swedish Cinema, 1908–2017 - Horak, Laura (European Journal of Scandinavian Studies, 2017)
Today’s explosion of Swedish films made by and about transgender people is sometimes considered in a vacuum. This article explores the long history of cross-gender performance in Swedish cinema and the relationship of these new films to older traditions. In this article, I will outline the contours of cross-gender performance in Swedish films from the 1908 to today, using some exemplary films to display the variety of styles, genres, and meanings that can be found: the short dance film Dances Through the Ages ( Skilda tiders danser , Walfrid Bergström, 1909); the swashbuckler Lasse-Maja (Gunnar Olsson, 1941); the romantic comedy Up With Little Märta ( Fram för Lilla Märta , Hasse Ekman, 1945); the dramatic art film The Magician ( Ansiktet , Ingmar Bergman, 1958); the recent romantic comedy Cockpit (Mårten Klingberg, 2012); and the trans art film Everything Falls Apart ( Nånting måste gå sönder , Ester Martin Bergsmark, 2016). I will show that the two main shifts in Swedish cinema’s representation of cross-gender performance occurred in the mid-1950s and in the 1990s, due to social changes and changes in the structure of the Swedish film industry. In Swedish cinema, as elsewhere, cross-dressing has never meant any one thing, so we must attend to the specific contexts of its expression in order to understand what it meant.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

Undercurrents: Queer Culture and Postcolonial Hong Kong - Hok-Sze Leung, Helen (UBC Press, 2009)
Undercurrents engages the critical rubric of "queer" to examine Hong Kong's screen and media culture during the transitional and immediate postcolonial period. Helen Hok-Sze Leung draws on theoretical insights from a range of disciplines to reveal parallels between the crisis and uncertainty of the territory's postcolonial transition and the queer aspects of its cultural productions. Leung explores Hong Kong cultural productions – cinema, fiction, popular music and subcultural projects – and argues that while there is no overt consolidation of gay and lesbian identities in Hong Kong culture, undercurrents of diverse and complex expressions of gender and sexual variance are widely in evidence. Undercurrents uncovers a queer media culture that has been largely overloo... Source: Publisher
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

The Gendered Screen: Canadian Women Filmmakers - Austin-Smith, Brenda; Melnyk, George (Wilfrid Laurier University Press, 2010)
Discussions of established women filmmakers whose careers have produced major bodies of work, as well as newer filmmakers and new media artists.
OCLC: 729021166
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Créatrice; _Nettoyé

New Black Queer Cinema - Wallenberg, Louise (New Queer Cinema: A Critical Reader, 2004)
In 1989, three years before the New Queer Wave was even invented or discovered, two very different yet interconnected films were produced on either side of the Atlantic. Both soon became critically successful and both would win a number of prizes at different international film festivals and venues. In retrospect, these two films have come to constitute the very incitement to the Wave. British filmmaker Isaac Julien’s Looking for Langston premiered in early 1989 and American filmmaker Marlon Riggs’s Tongues Untied premiered later that same year, the latter including a still photo from the former so as to pay homage
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Our Stories Have Never Been Told: Preliminary Thoughts on Black Lesbian Cultural Production as Historiography in The Watermelon Woman - Richardson, Matt (Black Camera, 2011)
Cheryl Dunye's 1996 film The Watermelon Woman earned a place in cinematic history as the first feature-length narrative film written and directed by an out black lesbian about black lesbians. This article examines how the film provides an important opportunity to mark the burgeoning genre of black queer documentary as a historiographical medium. The documentary film is a tool that highlights underexplored issues in black experience and provides a cultural site for imagining new possibilities for black lesbian subjectivity and creating innovative approaches to representing sexuality in black filmmaking.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Pink Dollars: Gay and lesbian Film Festivals and the Economy of Visibility - Rhyne, Ragan (2007)
This dissertation is about gay and lesbian film festivals, the first of which was founded in San Francisco in 1977 and subsequently served as a model for their international proliferation over the next thirty years. While the films programmed in these festivals have received a great deal of attention from scholars and critics, the festival institution itself has received less consideration. This dissertation narrates the history of gay and lesbian film festivals through an economic lens, asking how fundraising practices have been deployed in the community building projects of festivals, how the administrative structures of festivals as nonprofit organizations have been leveraged by the state toward the management of new social movements, and how these nonprofits have participated in the identification and cultivation of populations as niche markets by the commercial sector. This historical schema will offer an alternative model for understanding queer image production, not through a textual analysis of those images, but through an examination of the material circumstances of their circulation and distribution. This dissertation is not simply about the ways that community organizations like film festivals have been strategically engaged by the state and the market in the management and exploitation of gays and lesbians, it argues that gays and lesbians themselves have articulated their politics, artistic practice, and discourse of community within (and against) the parameters defined by the demands of organizational sustainability. Furthermore, this dissertation will illustrate why taking economic activity seriously as a part of the material practices of queer image production answers crucial questions about the ways that sexuality operates as a category of governance. The history of gay and lesbian film festivals, and their regulation through the administrative structures of the nonprofit sector, is part of a much larger history of political struggle and the development of new social movements over the past three decades.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

New Queer Cinema and Lesbian Films - Pick, Anat (New Queer Cinema: A Critical Reader, 2004)
The immediate aim of this chapter is to provide a critical overview of the place of lesbian films within New Queer Cinema. The task is not an easy one in a field which is as contentious as it is broad. The main difficulty seems to be how best to approach a range of definitions, from ‘new’ to ‘queer’ to ‘lesbian’, since with every one of them, we risk biting off more than we can chew. As often happens with formal titles, so with the New Queer Cinema, its lifespan (‘officially’ 1992-2000) now seems to have been a great deal shorter
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Struggles for Representation: African American Documentary Film and Video - Reid, Mark A. (American Literature, 2000)
Struggles for Representation examines over 300 non-fiction films by more than 150 African American film/videomakers and includes an extensive filmography, bibliography, and excerpts from interviews with film/videomakers. In eleven original essays, contributors explore the extraordinary scope of these aesthetic and social documents and chart a previously undiscovered territory: documentaries that examine the aesthetic, economic, historical, political, and social forces that shape the lives of black Americans, as seen from their perspectives.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Lesbian "Making-of" Documentaries and the Production of Lesbian Sex - Hankin, Kelly (The Velvet Light Trap, 2004)
The Velvet Light Trap 53 (2004) 26-39 On December 2, 2001, HBO began airing Project Greenlight, a twelve-part documentary series chronicling the production of a feature film by novice writer-director Pete Jones. With its spectacle of backroom dealings, unchecked egos, and human frailties, the television series capitalized on the contemporaneous success of like-minded "reality" programs such as Survivor and Temptation Island. Perhaps more closely, Project Greenlight also tapped into the current vogue for the "behind-the-scenes" and the "making-of" genres, represented by straight-to-video titles such as Star Trek-Deep Space Nine: Behind the Scenes (1993), Making of Jurassic Park (1995), and The Matrix Revisited (2001), television programs such as the Sundance Channel's Anatomy of a Scene, HBO's First Look, and MTV's Making the Video, and the proliferation of behind-the-scenes and making-of packaging on DVDs. A reflection of the growth of film-related ancillary products in the 1980s, the ever-expanding Hollywood ego, and the demands of a twenty-four-hour television cable market, the increased appearance of the making-of documentary format no doubt also reflects the renewed interest in amateur filmmaking promulgated by the age of desktop video. Perhaps as a manifestation of this interest, making-of documentaries have become increasingly more detailed in their coverage. Whereas the 1981 television special The Making of "Raiders of the Lost Ark" (Phillip Schuman) focuses mostly on the film's stunt work, special effects, location shoots, and set design, the recently released making-of documentary The Matrix Revisited focuses on script development, preproduction, production, postproduction, and exhibition, introducing viewers to costume designers, storyboard artists, and editors along the way. This attention to production detail can also be seen in Sundance's Anatomy of a Scene, which hones in on the construction, from music to costume to camera work, of a single scene. And certainly raising the bar on the level of detail included in the making-of genre is Project Greenlight, which is a "warts-and-all" look at film production, from squabbles over budgets to catering fiascos. Despite the making-of video's increased attention to the minutiae of filmmaking, one of the areas that remains outside the purview of most Hollywood making-of documentaries is the production of sex. Discussions about the cinematic logistics of creating a sex scene—how, when, and with what resources—are usually not featured in making-of documentaries. Of course, given our celebrity-driven culture, the question of sex vis-à-vis film production, particularly a Hollywood film production, is hardly absent from the publicity that surrounds a film. It is not uncommon to hear actresses or actors discussing what it was like to kiss another actor on the set. But these kinds of concerns are usually the province of entertainment magazines and television, not the province of ancillary related products such as the making-of video. While stories of roles requiring nudity or sex scenes abound on television shows such as Access Hollywood, Entertainment Tonight, and E! News Daily,these kinds of topics are less likely to appear in production-generated documentaries. Indeed, while the production of the provocative sex scene between Halle Berry and Billy Bob Thornton in Monster's Ball (Marc Forster, 2001) generated much discussion on television entertainment programs, talk shows, and newsmagazines, it was the film's prison execution sequence that was featured in the Sundance Channel's making-of special on the film. Given the lack of focus on sex scenes in most making-of documentaries, it is interesting to note that the two existing making-of documentaries for lesbian-made, lesbian-themed feature films—The Making of Bar Girls (1995) and Moments: The Making of Claire of the Moon (1992)—both heavily focus on the production of lesbian sex. Moreover, both lesbian making-of documentaries emphasize the cast's and the crew's sexual titillation over the creation of sexual sequences. In this essay I look at what this strategy reveals about the collective climate and concerns of lesbian feature filmmaking in the United States today.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Examining Professional and Academic Culture in Chilean Journalism and Mass Communication Education - Mellado, Claudia (Journalism Studies, 2011)
This article discusses key findings from a survey of the professional patterns, scholarly productivity, and educational characteristics of Chilean Journalism and Mass Communication (JMC) educators, as well as documentary information about the schools where they work. The results reveal a weak academic culture that contrasts with a strong professional culture among the members of this community, but also the influence that both organizational and individual variables have on Chilean JMC educators' orientations. Specifically, the analyses indicated that the level of education, part-time/full-time commitment, and the type of university are the most influential factors in defining both the prevalence of a professional culture and the lack of research productivity. These findings support other international studies, indicating a global tendency across key variables that influence academic development in the field. Likewise, it shows how distant Chilean JCM educators are from the university-scholarly tradition.
_eprint: https://doi.org/10.1080/1461670X.2010.507373
Keywords: 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12047
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Num Pages: 65-77 Place: Austin, United States
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Tracing the History of Trans and Gender Variant Filmmakers - Horak, Laura (Spectator: The University of Southern California Journal of Film & Television, 2017)
Most writing on transgender cinema focuses on representations of trans people, rather than works made by trans people. This article surveys the history of trans and gender variant people creating audiovisual media from the beginning of cinema through today. From the professional gender impersonators of the stage who crossed into film during the medium’s first decades to selfidentified transvestite and transsexual filmmakers, like Ed Wood and Christine Jorgensen of the mid-twentieth century, to the enormous upsurge in trans filmmaking of the 1990s, this article explores the rich and complex history of trans and gender variant filmmaking. It also considers the untraceable gender variant filmmakers who worked in film and television without their gender history becoming known and those who made home movies that have been lost to history.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 5-Créateur.rice LGBTQ+; _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Num Pages: 297-300
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Num Pages: 25-40
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema/Ethereal Queer: Television, Historicity, Desire - Betancourt, Manuel (Film Quarterly, 2013)
Betancourt reviews The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema by Nick Davis and Ethereal Queer Television, Historicity, Desire by Amy Villarejo.
Num Pages: 95 Place: Berkeley
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Contemporary Greek Film Cultures from 1990 to the Present - Kazakopoulou, Tania; Fotiou, Mikela (Peter Lang Ltd, International Academic Publishers, 2017)
This collection of new writing on contemporary Greek cinema builds and expands on existing work in the field, providing a coherent analysis of films which, despite their international importance, have so far received limited critical attention. The volume maps key trends in Greek cinema since the 1990s within the wider context of production and consumption at both national and international levels. It offers a wide range of critical analyses of documentary and avant-garde filmmaking, art house and popular cinema, and the work of established and new directors as well as deliberations on teaching methodologies and marketing strategies. The book seeks to highlight the continuities, mutual influences and common contexts that inform, shape and inspire filmmaking in Greece today.
Issue: vol. 21
Keywords: 1-Cinéma; 2-Muséologie critique; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

The View from here Conversations with Gay and Lesbian Filmmakers - Hays, Matthew (Arsenal Pulp Press, 2007)
The history of gay and lesbian cinema is a storied one, and became that much larger with the recent success of Brokeback Mountain. But the history of gay and lesbian filmmakers is its own story. In The View From Here, queer directors and screenwriters speak passionately about the medium, in particular their personal experiences navi-gating the often cynical and cruel film industry. All of them offer fascinating anecdotes and ideas about cinema, and speak candidly about their attempts to combat studio apathy and demands of “the market” to create films that are entertaining, engaging, and truthful.
Pages: 1 vol. (383 p.) :
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Identity and Performance in Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography - Heitner, Devorah (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In novel ways, and from a surprising location, Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography (1995) explores some of the same dilemmas that earlier African American expatriate artists promulgated, using their time abroad as a win dow onto America, while relishing the nurturing possibilities of partial escape from American racism. Some of the most complex and insightful observations about America and American racism have been crafted by African American expatriate artists such as James Baldwin and Josephine Baker. These artists’ depictions of their encounters abroad complicate our understandings of American identity and American racism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Queer Times, Black Futures - Kara Keeling (New York University Press, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

The Kids Are Not All Right: The Curious Case of Sapphic Censorship in City-State Singapore - Chen, Loretta (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer examines Singapore's Media Development Authority's censorship of representations of lesbianism in film, music video, television and theatre. She highlights the government surveillance and repression of portrayals of LGBT cultures and communities in Singapore by unpacking the ambiguities and contradictions underlying the censorship of these popular media forms. This reflects an institutional ‘inability to read lesbians’.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Hollywood at the Intersection of Race and Identity - Konzett, Delia Caparoso. (Rutgers University Press, 2020)
Hollywood at the Intersection of Race and Identity explores the ways Hollywood represents race, gender, class, and nationality at the intersection of aesthetics and ideology and its productive tensions. This collection of essays asks to what degree can a close critical analysis of films, that is, reading them against their own ideological grain, reveal contradictions and tensions in Hollywood’s task of erecting normative cultural standards? How do some films perhaps knowingly undermine their inherent ideology by opening a field of conflicting and competing intersecting identities? The challenge set out in this volume is to revisit well-known films in search for a narrative not exclusively constituted by the Hollywood formula and to answer the questions: What lies beyond the frame? What elements contradict a film’s sustained illusion of a normative world? Where do films betray their own ideology and most importantly what intersectional spaces of identity do they reveal or conceal?
Pages: ix, 357 pages :
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

DV-made Tibet: Domestic Videos, Elite Films, and the Work of Pema Tseden - Barnett, Robert (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In the three decades after 1980, major changes took place in the ways in which culture in Tibet was produced, transmitted, and consumed.¹ These changes, however, were not evidence of the radical transformation often claimed as the result of digitization, but were brought about by earlier forms of technological development. In terms of music and radio, it was the arrival of cheap cassette players and recorders in Tibet in the late 1980s that allowed Tibetans to choose for the first time when to listen and, within the limits allowed by the market and the government, what to listen to (Dhondup
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

APPENDIX II: Tibetan Filmography/Videography - Barnett, Robert; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

APPENDIX I: Chinese and Non-Chinese Filmography/Videography - Cho, Ting-Wu; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Chinese Independent Cinema in the Age of “Digital Distribution” - Gao, Dan (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
My chapter looks at Chinese independent cinema as an institutionalizing enterprise. In other words, although many filmmakers keep emphasizing the individualistic quality of their agenda or the idiosyncrasy of their film works, independent films have developed things in common, such as certain thematics, addresses, formalistic styles, and modes of production. Their survival is also predicated more and more on shared infrastructures of film communities, distribution agents, and exhibition networks. Of course, this does not mean that the institution of Chinese independent cinema is settled and finalized; it isn’t like a breed of crops circled by impermeable ideological or physical fences.
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Chinese Digital Shadows: Hybrid Forms, Bodily Archives, and Transnational Visions - Reynaud, Bérénice (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Taking Hao Jie’s Single Man as a case study, this chapter discusses the effect of globalization on independent DV production—a home-grown phenomenon born out of the availability of DV cameras and computer editing software and the spreading of the internet. Starting as a marginalized practice without access to the domestic market, and expressing a desire to saturate the visual field with obfuscated images and to create a counter-archive (a counter-memory of the Chinese people), it attracted international attention, which in turn allowed it to have access to alternative forms of financing as well as the input of foreign talent. The fluidity of digital modes of production also contributed to an eradication of the boundaries between documentary and fiction. Instead, the real divide lies between “the desire for cinema” and “the desire for documentation.”
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Recalcitrance of Reality: Performances, Subjects, and Filmmakers in 24 City and Tape - Wang, Qi (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Since its beginning in the early 1990s, independent Chinese documentary has steadily built a reputation with its unflinching presentation of the underbelly of China’s economic boom and social sea changes. Individuals and groups whose experiences register the drastic costs of this process have become the most natural and common subject matter of independent documentaries. From the struggling artists who were among the first to quit state employment and go independent in Bumming in Beijing (Wu Wenguang 1990) to the art-aspiring young migrants from the rural area in The Other Bank (Jiang Yue 1995), from the homeless youngsters in Along the
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

Toward a Digital Political Mimesis: Aesthetic of Affect and Activist Video - Zhen, Zhang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Section: 10 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch10
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave Macmillan, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé